Happier on The Job: A Pleasant Experience by Logistic Employee of Logistics Surabaya - Bisma Arianto; Siti Samsiyah; Laila Arkadia (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2022)
Abstract. This is a quantitative study Happier on the job is the feeling and attitude of employees towards the work they are currently engaged in. APM Logistics firm of the Surabaya branch is a company in the field of services that provides package delivery, documents, moving, and warehousing services that were founded in 1990. This study to describe the level of satisfaction obtained by PT. APM Logistik Surabaya branch in terms of financial compensation, work discipline, and work loyalty. Respondents for this study used a sample of 60 employees. The instrument collected in data collection is a questionnaire consisting of 51 statement items that must be answered by the respondent. The data analysis used is assumption test, multiple linear regression, t test and F test. This study has some variables such as financial compensation, discipline and loyalty as independent variables; and job satisfaction as the dependent variable. This study concluded that financial compensation has got a positive and meaningful effect on employee job satisfaction, work discipline have got a positive and significant effect on job satisfaction, loyalty has a significant effect on job satisfaction. Meanwhile, financial compensation, work discipline, and work loyalty simultaneously have a effect on job satisfaction. The authors suggestion companies need to take notice to the provision of proper and fair financial compensation to their employees on their workload. Keywords: compensation, discipline, loyalty, satisfaction, employees.